2006
DOI: 10.1634/stemcells.2006-0011
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation Modulates Fate Determination of Differentiating Embryonic Stem Cells

Abstract: A clear understanding of cell fate regulation during differentiation is key in successfully using stem cells for therapeutic applications. Here, we report that mild electrical stimulation strongly influences embryonic stem cells to assume a neuronal fate. Although the resulting neuronal cells showed no sign of specific terminal differentiation in culture, they showed potential to differentiate into various types of neurons in vivo, and, in adult mice, contributed to the injured spinal cord as neuronal cells. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
134
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(140 citation statements)
references
References 40 publications
6
134
0
Order By: Relevance
“…They found that while the transplanted EBs differentiated into neurons in the injured spinal cord at a higher frequency than the transplanted EBs without electrical stimulation, the proliferative capacity of the electrically stimulated EBs was lower than that of the non-stimulated EBs. Thus, this method was effective from the aspect of safety, but did not lead to satisfactory recovery of motor function after SCI [29]. None of these studies has clarified exactly which stage of induction from ES cells to NS/PCs contained in the neurospheres would be the most suitable for transplantation therapy at the subacute phase of SCI.…”
Section: Transplantation Of Mouse Es Cell-derived Ns/pcs Into the Injmentioning
confidence: 98%
See 1 more Smart Citation
“…They found that while the transplanted EBs differentiated into neurons in the injured spinal cord at a higher frequency than the transplanted EBs without electrical stimulation, the proliferative capacity of the electrically stimulated EBs was lower than that of the non-stimulated EBs. Thus, this method was effective from the aspect of safety, but did not lead to satisfactory recovery of motor function after SCI [29]. None of these studies has clarified exactly which stage of induction from ES cells to NS/PCs contained in the neurospheres would be the most suitable for transplantation therapy at the subacute phase of SCI.…”
Section: Transplantation Of Mouse Es Cell-derived Ns/pcs Into the Injmentioning
confidence: 98%
“…Keirstead et al [28] established an effective method of inducing human ES cells to differentiate into highly pure populations of oligodendrocyte progenitors by using a culture medium containing factors promoting differentiation into oligodendrocytes, such as insulin and thyroid hormones, and reported that the transplantation of these oligodendrocyte progenitors into the injured spinal cord of rats resulted in remyelination of demyelinated axons and recovery of motor function. Subsequently, Yamada et al [29] used electrically stimulated mouse EBs generated from ES cells to induce selective differentiation into neurons for transplantation into the injured spinal cord. They found that while the transplanted EBs differentiated into neurons in the injured spinal cord at a higher frequency than the transplanted EBs without electrical stimulation, the proliferative capacity of the electrically stimulated EBs was lower than that of the non-stimulated EBs.…”
Section: Transplantation Of Mouse Es Cell-derived Ns/pcs Into the Injmentioning
confidence: 99%
“…They reported the remyelination of demyelinated axons and hind limb function recovery when they transplanted these cells into the injured spinal cords of rats. Later, Yamada et al [27] formed EBs from ES cells and transplanted them into injured spinal cords, after applying an electrical stimulus to the EBs that caused the selective induction of neuronal differentiation. These authors found that a higher proportion of the electrically induced EBs differentiated into neurons than did control EBs.…”
Section: Transplantation Of Mouse Es Cell-derived Neural Stem/progenimentioning
confidence: 99%
“…Electric fields are known to be related to the neuronal differentiation of embryonic, neural and mesenchymal stem cells 4,25,42,45 . It is possible that the differentiation process can take place also when stimulating cells with electric field only but the upregulation of beta-tubulin isotype III, a marker for immature neurons, was seen only after 14 days of culture, compared to 4 days when using electric field and copper together.…”
Section: Discussionmentioning
confidence: 99%
“…In stem cells, elongation and other morphological changes are often related to differentiation 34 . It has been shown that the electric field stimulation of neuronal pre-differentiated embryonic stem cells remarkably increases their differentiation 45 . In addition, Matos et al reported the different effects of alternating electric fields, which were applied through nickel electrodes, on neural stem cell viability and differentiation 25 .…”
Section: Introductionmentioning
confidence: 99%